VARIASI PEMBELAJARAN KESENIAN DI SMA LAB SCHOOL BANDA ACEH TAHUN AJARAN 2012/2013 - Ramdiana - (Mentari: Majalah Ilmiah Universitas Muhammadiyah Aceh, 2013)
The research objective was to determine teacher competence Culture Arts Lab School High School Syiah Kuala University held a variety of teaching and learning in teaching both theoretical and practical learning. Subjects were two teachers Cultural Arts Lab School High School Syiah Kuala University who teach in class VII, VIII and IX. Data collection techniques used were observation of learning activities using video. The method selected for video recording with video recording makes it possible to analyze the complexity of learning activities gradually and more accurate. Learning activities are recorded in full without audited. For the purposes of video analysis initially transferred to a CD. The next step for the preparation of the analysis was transcribing video.Â  After that video recordings were analyzed using categories defined as follows: 1) variations in the way of teaching; 2) variations in the use of media and teaching tools; 3) variations in patterns of interaction and student activities. The results observation of learning activities using video two teachers Cultural Arts Lab School High School Syiah Kuala University who teach in class VII, VIII and IX it can be concluded that: (1) hold a variety of teacher competence in teaching including both categories and the need for improvement in aspects of focusing students; (2) hold a variety of teacher competence in the use of media and teaching tools include both categories; (3) the competence of teachers held a variety of interaction patterns and student activities include both categories, there is need for improvement in aspects of students' patterns of interaction and activity between the teacher-student and patterns of teacher-student-teacher.Â Keyword: observation, data collection, analysis, and concludedÂ